Efficient heterogeneous copper fluorapatite (CuFAP)-catalysed oxidative synthesis of diaryl sulfone under mild ligand- and base-free conditions - Kamble, R. B.; Chavan, S. S.; Suryavanshi, G. (New Journal of Chemistry, 2019)
A simple, eco-friendly and efficient method for the synthesis of unsymmetrical diaryl sulfones using heterogeneous copper fluorapatite (CuFAP)-catalysed coupling of aryl sulfonic acid and phenyl boronic acid has been developed with good to excellent yields without use of any ligand, base or co-catalyst. Broad substrate scope and gram scale operations are the important features of this method.